Controlled reproduction in Anguilla anguilla (L.): advanced studies on broodstock management, spawning techniques and system design for artificial seed production. - Di Biase, Andrea <1979> (Alma Mater Studiorum - Università di Bologna, 2015)
The thesis aims to expose the advances achieved in the practices of captive breeding of the European eel (Anguilla anguilla). Aspects investigated concern both approaches livestock (breeding selection, response to hormonal stimulation, reproductive performance, incubation of eggs) and physiological aspects (endocrine plasma profiles of players), as well as engineering aspects. Studies conducted on various populations of wild eel have shown that the main determining factor in the selection of wild females destined to captive breeding must be the Silver Index which may determine the stage of pubertal development. The hormonal induction protocol adopted, with increasing doses of carp pituitary extract, it has proven useful to ovarian development, with a synchronization effect that is positively reflected on egg production. The studies on the effects of photoperiod show how the condition of total darkness can positively influence practices of reproductions in captivity. The effects of photoperiod were also investigated at the physiological level, observing the plasma levels of steroids ( E2, T) and thyroid hormones (T3 and T4) and the expression in the liver of vitellogenin (vtg1 and vtg2) and estradiol membrane receptor (ESR1). From the comparison between spontaneous deposition and insemination techniques through the stripping is inferred as the first ports to a better qualitative and quantitative yield in the production of eggs capable of being fertilized, also the presence of a percentage of oocytes completely transparent can be used to obtain eggs at a good rate of fertility. Finally, the design and implementation of a system for recirculating aquaculture suited to meet the needs of species-specific eel showed how to improve the reproductive results, it would be preferable to adopt low-flow and low density incubation. : L’elaborato presentato si propone di esporre gli avanzamenti conseguiti nelle pratiche di riproduzione in cattività dell’anguilla europea (Anguilla anguilla). Gli aspetti indagati riguardano sia approcci zootecnici (selezione riproduttori, risposta a stimolazione ormonale, performance riproduttive, incubazione di uova) sia aspetti fisiologici (profili endocrini plasmatici dei riproduttori), nonché aspetti ingegneristici. Gli studi condotti sulle diverse popolazioni selvatiche di anguilla hanno evidenziato come il principale fattore discriminante nella selezione delle femmine selvatiche da destinare alla riproduzione in cattività deve essere il Silver Index che ne può determinare, a partire caratteri morfo-metrici e con un chiaro grado di precisione, lo stadio di sviluppo puberale. Il protocollo di induzione ormonale adottato, con dosi crescenti di estratto ipofisario di carpa, si è dimostrato utile allo sviluppo ovarico, con un effetto di sincronizzazione che si è positivamente riflesso sulla produzione di uova. Gli studi sugli effetti del fotoperiodo dimostrano come la condizione di totale buio, nelle vasche di mantenimento dei riproduttori, condizioni positivamente le pratiche di riproduzioni in cattività.. Gli effetti del fotoperiodo sono stati indagati anche a livello fisiologico, osservando i livelli plasmatici di steroidi (E2, T) e ormoni tiroidei (T3 e T4) nonché l’espressione a livello epatico dello vitellogenine (vtg1 e vtg2) e del recettore di membrana dell’estradiolo (esr1). Dalla comparazione fra deposizione spontanea e tecniche di inseminazione attraverso lo stripping si è dedotto come la prima porti ad una migliore resa qualitativa e quantitativa nella produzione di uova atte ad essere fecondate, inoltre la presenza di una percentuale di ovociti completamente trasparenti può essere utilizzato per ottenere le uova ad un buon tasso di fertilità. Infine, il design e la messa in opera di un impianto a ricircolo per l’acquacoltura adatto a soddisfare le necessità specie-specifiche dell’anguilla ha mostrato come per migliorare i risultati riproduttivi, sarebbe preferibile adottare basso flusso e bassa densità incubazione.